Characteristics of three strains of avian adenoviruses isolated in Queensland. I. Biological properties - Mustaffa Babjee, Ahmad; Spradbrow, P. B. (American Association of Avian Pathologists, 1975)
Three strains of avian adenovirus were isolated and studied in cell cultures, chicken embryos, and chickens. One strain (ADAM-1) was isolated from the bursa of Fabricius of a chicken with Marek's disease, and the others (ADAM-2 and ADAM-3) from one-day-old chicks with respiratory signs. Experimentally, ADAM-1 produced no clinical signs or lesions except atrophy of the bursa of Fabricius. ADAM-2 caused mild respiratory signs in young chickens when inoculated intratracheally. The behavior of the three viruses in cell cultures and chick embryos was similar to that described for other avian adenoviruses (CELO). In a serological survey using the agar-gel precipitation test, 3-30% of sera tested gave a positive reaction.